ROP18 Is a Key Factor Responsible for Virulence Difference between Toxoplasma gondii and Neospora caninum - Lei, Tao (Public Library of Science, 2014)

(untitled)
Toxoplasma gondii (T. gondii) and Neospora caninum (N. caninum) are both obligate intracellular protozoan parasites and share many common morphological and biological features. Despite these similarities the two parasites differ dramatically in virulence in mice, but the factors involved in virulence differences between the two parasites remain unknown. A secreted serine-threonine kinase called rhoptry protein 18 (ROP18) was identified to play a crucial role on virulence differences among different T. gondii clonal lineages. Intriguingly, we found that ROP18 in Nc1 strain of N. caninum (NcROP18) is a pseudogene due to several interrupting stop codons in the sequence in our previous studies. We assume that the difference of ROP18 leads to virulence difference between T. gondii and N. caninum. We constructed a transgenic N. caninum Nc1 stain by transfecting the TgROP18 from the T. gondii RH strain. Phenotype and virulence assays showed that the expression of TgROP18 in N. caninum did not affect the motility and cell invasion, but resulted in a significant increase in intracellular parasite proliferation and virulence in mice. Immunity-Related GTPase (IRG) phosphorylation assay showed that the transgenic parasite Nc1-TgROP18 was able to phosphorylate IRGs as T. gondii did. The present study indicated that the ROP18 plays a crucial role in virulence of the closely related parasites T. gondii and N. caninum and it is indeed a key factor responsible for the virulence difference between T. gondii and N. caninum.